Proteomics Analysis of the Regulatory Mechanism of the Calcium-Independent Phospholipase A2 Activity of Peroxiredoxin 6 on Beef Tenderization - LIU Jitong, WANG Xinyi, ZHANG Yimin, ZHU Lixian, LIANG Rongrong, MAO Yanwei (Shipin Kexue)
To elucidate the effect of the calcium-independent phospholipase A2 (iPLA2) activity of peroxiredoxin 6 (Prdx6) on beef tenderization and the underlying mechanism of action during the postmortem aging process, we investigated the specific role of Prdx6 as a biomarker in beef tenderization. In this study, we determined the changes in myofibrillar protein particle size during postmortem aging to observe myofibrillar protein degradation, and explored the changes in intrinsic differential proteins using tandem mass tag (TMT)-based quantitative proteomics. The results showed that the degradation of myofibrillar proteins in beef was promoted after incubation with MJ33, an inhibitor of iPLA2 activity of Prdx6, for 24 h. A total of 336 differential proteins were identified by proteomics analysis in the Con (normal saline) vs G0 (unincubated), MJ33 vs G0, and MJ33 vs Con groups, with the core ones being PRDX6, SOD1, GPX1 and PARK7. These differential proteins were primarily enriched in glycolysis, the apoptosis signaling pathway and cytoskeletal proteins and were predominantly located in the cytoplasm. However, the differential proteins between the MJ33 and Con groups were mainly concentrated in the cell membrane. Interactions existed among some differential proteins, which were mainly enriched in cellular antioxidant defense, ribosome-mediated protein synthesis regulation, and phospholipid functions. It is suggested that inhibiting Prdx6 iPLA2 activity might impact the degradation of myofibrillar proteins by mediating membrane function, energy metabolism, and apoptosis, ultimately accelerating beef tenderization.